Comparative Assessment of Functional Recovery Following Dynamic Hip Screw Plate versus Proximal Femoral Nail Fixation in the Management of Unstable Trochanteric Fractures of the Femur - Avik Kumar Khanra; Indrajit Sardar; Tapendra Nath Sarkar; Rajiv Chatterjee (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Unstable trochanteric fractures include posteromedial comminution, reverse oblique pattern, lateral wall fracture and subtrochanteric extension. Unstable trochanteric fractures usually can be treated by anatomical reduction with the use of a sliding hip screw or cephalomedullary nail. DHS is cost-effective and user-friendly whereas PFN, though biomechanically superior, is a relatively new entrant. Thus this comparative study helped us to understand the management of unstable trochanteric fractures in terms of surgical technique and evaluate the functional outcomes after fixation with PFN and DHS. Aims and Objectives: To compare the functional outcome, safety and effectiveness of dynamic hip screw plate (DHS) and proximal femoral nail (PFN) fixation in the management of unstable trochanteric fractures of femur. Materials and Methods: The study was an observational longitudinal follow up comparative study. 50 adult patients of age group 40 to 80 years having unstable trochanteric fractures of femur treated with either DHS plate or PFN were included in the study. 27 such patients were operated with DHS whereas 23 patients were operated with PFN. Modified Harris hip score, duration of hospitalisation, presence or absence of abduction lurch, intraoperative blood loss and procedure time and time to independent mobility were compared between the two groups during postoperative follow up. Results: Patients treated with PFN had better outcome than DHS in terms of shorter duration of hospitalisation, early mobilization in terms of early pain-free full weight bearing, lesser intraoperative blood loss, shorter procedure time and better functional result on the basis of modified Harris hip score at final follow up. But, PFN fixation was associated with more abduction lurch compared to DHS. Conclusion: Thus, PFN proved to be a better implant than DHS in the management of unstable trochanteric fractures of femur.